Congenital muscular dystrophies and myopathies: the leading cause of genetic muscular disorders in eleven Chinese families - Bin Mao; Xiaoling Cai; Na Lin; Yulin Jiang; Na Hao; Yifang Dai; Danhua Guo; Deqin He; Huili Xue; Lingji Chen; Qianqian He; Min Zhang; et al. (BMC Musculoskeletal Disorders)
Abstract Background Congenital muscular dystrophies (CMDs) and myopathies (CMYOs) are a clinically and genetically heterogeneous group of neuromuscular disorders that share common features, such as muscle weakness, hypotonia, characteristic changes on muscle biopsy and motor retardation. In this study, we recruited eleven families with early-onset neuromuscular disorders in China, aimed to clarify the underlying genetic etiology. Methods Essential clinical tests, such as biomedical examination, electromyography and muscle biopsy, were applied to evaluate patient phenotypes. Whole exome sequencing was used to screen for prospective variants responsible for muscular diseases, followed by co-segregation analysis in the families and prenatal diagnosis via Sanger sequencing, if appropriate. Nanopore sequencing and optical genome mapping were applied for detecting complicated genome rearrangements. Results Fourteen variants in nine genes (ATL1, LMNA, KLHL40, FKRP, DMD, ACTA1, MSTO1, RYR1 and LAMA2) associated with congenital muscular conditions were identified in the ten families mentioned above. Among them, five novel variants, c.1153_1155del in LMNA, c.577 A > G in ACTA1, c.694T > G in MSTO1, c.5938del in LAMA2, and a rare genome fusion ogm[GRCh38] fus(X; X)(p22.31;p21.1) involving DMD, have not been recorded in public databases to the best of our knowledge. Conclusions CMDs and CMYOs were probably responsible for most of the cases (9/11) of genetic muscular defects in this study. Molecular analysis is highly beneficial for the precise diagnosis, genetic counseling and prenatal diagnosis of families suspected of having genetic muscular disorders. Clinical trial number Not applicable.